Observation of isoscalar multipole strengths in exotic doubly-magic 56Ni in inelastic α scattering in inverse kinematics - S. Bagchi; J. Gibelin; M.N. Harakeh; N. Kalantar-Nayestanaki; N.L. Achouri; H. Akimune; B. Bastin; K. Boretzky; H. Bouzomita; M. Caamaño; L. Càceres; S. Damoy; et al. (Physics Letters B, 2015)
The Isoscalar Giant Monopole Resonance (ISGMR) and the Isoscalar Giant Dipole Resonance (ISGDR) compression modes have been studied in the doubly-magic unstable nucleus 56Ni. They were measured by inelastic α-particle scattering in inverse kinematics at 50 MeV/u with the MAYA active target at the GANIL facility. The centroid of the ISGMR has been obtained at Ex=19.1±0.5 MeV. Evidence for the low-lying part of the ISGDR has been found at Ex=17.4±0.7 MeV. The strength distribution for the dipole mode shows similarity with the prediction from the Hartree–Fock (HF) based random-phase approximation (RPA) [1]. These measurements confirm inelastic α-particle scattering as a suitable probe for exciting the ISGMR and the ISGDR modes in radioactive isotopes in inverse kinematics.